2019
DOI: 10.3174/ajnr.a6203
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioidomycosis of the Central Nervous System: CT and MR Imaging Findings

Abstract: BACKGROUND AND PURPOSE: Paracoccidioidomycosis is a fungal infection mainly caused by the thermodimorphic fungus Paracoccidioides. The purpose of our study was to demonstrate the neuroimaging findings from 24 patients with CNS paracoccidioidomycosis. MATERIALS AND METHODS:We performed a retrospective analysis focusing on the radiologic characteristics of CNS paracoccidioidomycosis. The 24 selected patients underwent MR imaging and/or CT, and the diagnosis was made by the presence of typical neuroimaging featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 36 publications
0
22
0
9
Order By: Relevance
“…Imaging studies using computerized tomography (CT) showed a prevalence of 12.5% for NPCM among PCM patients without neurologic symptoms [ 11 ]. The increase in the availability and quality of imaging tests, when combined with the epidemiology and clinical manifestations, enabled a greater number of diagnoses [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Imaging studies using computerized tomography (CT) showed a prevalence of 12.5% for NPCM among PCM patients without neurologic symptoms [ 11 ]. The increase in the availability and quality of imaging tests, when combined with the epidemiology and clinical manifestations, enabled a greater number of diagnoses [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging and CT scan besides helping in the NPCM diagnosis are important to locate and characterize the neural lesions. The cerebral hemispheres are affected in 62.5–65.0%, the cerebellum in 25.0–33.3%, the brain steam in 8.3–25.0%, and the spinal cord in 4.0% [ 8 , 12 ]. Our findings are in accordance with the literature data showing predominance of the involvement of the cerebral hemispheres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential diagnosis includes Coccidioides immitis (sporangia measuring 30 µm to 60 µm and containing 1 µm to 5 µm sporangiosporesit usually occurs as meningitis), Histoplasma capsulatum (a dimorphic, ovoid fungi, measuring 2 µm to 5 µm), and Cryptococcus neoformans (yeasts measuring 4 µm to 7 µm and exhibiting a mucinous capsule). 1,2,7,12,13,19,20,22 In the presence of the pseudotumorous form of NPDM, the differential diagnosis also includes neoplasms (primary and secondary), abscesses, tuberculosis, and neurocysticercosis. 7,12,13,19,20,[22][23][24] The therapy includes sulfonamides, amphotericin B and azoles (fluconazole, itraconazole, voriconazole).…”
Section: Discussionmentioning
confidence: 99%
“…Resto del examen bajo la normalidad. Al ingreso con los siguientes exámenes de laboratorio, en el hemograma: leucocitos 17,600/mm 3 , neutrófilos 14,200/mm 3 , linfocitos 2,400/mm 3 10, 8%, eosinófilos 300/mm 3 , plaquetas 513,000/mm 3 , hemoglobina 13,8 gr/dl, hematocrito 42,4%; función renal con creatinina 0,68 mg/dl y BUN 20,1 mg/dl; función hepática con AST 2, 280 U/L (valor de referencia 0-40 U/L) y ALT 1,800 U/L (valor de referencia 0-33 U/L); tiempo de coagulación con un PT 9,8 seg (9,(7)(8)(9)(10)(11)8 Se hospitalizó para realizar estudios de extensión con impresión diagnóstica de síndrome cruzado de tallo cerebral a nivel mesencefálico medial posiblemente secundario a lesión tumoral o enfermedad infecciosa expansiva. Al día siguiente, se valoró por Neurología quien consideró tomar tomografía axial computarizada (TAC) con contraste, que permitió identificar lesión hipodensa con realce en anillo a nivel frontal, además compromiso a nivel del tálamo, protuberancia, mesencéfalo del lado izquierdo acompañándose de edema con efecto compresivo local.…”
Section: Presentación De Casounclassified